2004
DOI: 10.1590/s0103-50532004000100016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Perna perna (Linné, 1758) as a tool to monitoring trace metals contamination in estuarine and coastal waters of Rio de Janeiro, Brazil

Abstract: Foram coletados espécimes de mexilhões Perna perna de diversas estações ao longo da costa do Rio de Janeiro e analisados os conteúdos de cobre, zinco, cádmio e cromo. Apesar da grande variabilidade nos organismos pertencentes à mesma população, a avaliação estatística permitiu a diferenciação através de níveis de metal traço entre regiões e estações de coleta assim como entre machos e fêmeas. Diferenças nos conteúdos de metais não confirmam as espectativas baseadas em fontes de contaminação e dados existentes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 9 publications
(12 reference statements)
4
13
0
6
Order By: Relevance
“…(Carvalho et al, 2001), and for Cr, Fe, Mn, Pb, and Zn (Carvalho et al, 2001;Ferreira et al, 2004). The present work also corroborates the high concentrations of Cd and Ni (Ferreira et al, 2004), and Zn (Francioni et al, 2004), observed in female mussels of P. perna.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…(Carvalho et al, 2001), and for Cr, Fe, Mn, Pb, and Zn (Carvalho et al, 2001;Ferreira et al, 2004). The present work also corroborates the high concentrations of Cd and Ni (Ferreira et al, 2004), and Zn (Francioni et al, 2004), observed in female mussels of P. perna.…”
Section: Resultssupporting
confidence: 88%
“…Females of P. perna showed significantly higher Cu levels than males (Figure 3). Similar results for Cu accumulation were observed for the coast of the Rio de Janeiro state, by Carvalho et al (2001) and Francioni et al (2004). Figure 3.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…39,40 It is considered one of the most degraded ecosystems of the Brazilian coast. 41 Several studies conducted in Guanabara Bay show environmental impacts such as eutrophication, 42,43 high sedimentation rates, 44,45 high concentrations of metals, [46][47][48][49][50][51] and hydrocarbons 25,27,30,52,53 in water, sediment and biota. Among the main sources of pollution to the bay, stand out more than 14,000 industries, domestic sewage discharges with low or no treatment, 14 oil terminals, 2 harbors, 32 boatyards and more than 1000 gas stations.…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…Os principais cultivos no Brasil ocorrem no estado de Santa Catarina devido a suas características oceanográficas (MARENZI & BRANCO, 2005). As características do mexilhão Perna perna favorecem a absorção e acúmulo de contaminantes, entre eles os poluentes orgânicos persistentes (FRANCIONI et al, 2007), metais (FRANCIONI et al, 2004) e fármacos (CORTEZ et al, 2012), além de absorverem micropartículas de plásticos, já observado na região da baía de Santos, gerando consequências em alterações fisiológicas do organismo (ASCER, 2015).…”
Section: )unclassified